Penciptaan Serial “AKURA-POPO” Episode “SAMPAH” Dengan Teknik Animasi Komputer 2D - Abidin Syamsul Arifin; Arif Sulistiyono; Mahendradewa Suminto (Institut Seni Indonesia Yogyakarta, 2017)
Trash is actually not a new problem on the planet. However, the handling is still less effective in various places around the world. But at least how humans try to reduce the minimum amount of waste. It is the human hand that actually creates the waste itself.The serial animation